Gestión administrativa- financiera en el cumplimiento presupuestario de la Universidad Técnica de Babahoyo, periodo 2013-2014, Implementación de una unidad de auditoría interna. - Escobar Mayorga, Diana Carolina (2015)
The Technical University of Babahoyo is located in Los Rios Province Babahoyo, its main mission is to provide quality education to students and warmth. This research evaluated the administrative and financial management in the budget implementation of the Technical University of Babahoyo. Different opinions of different authors that helped them extend the theoretical framework of the research were analyzed. The method of analysis and synthesis was used surveys and interviews conducted by 32 people, the same as those represented by officials and administrative personnel in the areas of finance, budget and treasury, that allowed evaluate how it has handled the administrative and financial management Technical University of Babahoyo in the period 2013-2014. Among the main results emerged that meeting effectiveness at the Technical University of Babahoyo has decreased based on the budget allocation provided by the government, the instrument that helped test the hypothesis of the research was quantitative analysis of the Chi test square, since the value does not exceed the critical value level. Based on the results of the proposed implementation of an internal audit unit, it will allow better control of processes and the allocation of resources to different programs or activities presented in the annual operating plan is presented.